Risk Factors for Peer Victimization among Middle and High School Students - Rebecca A. Vidourek; Keith A. King (MDPI AG, 2019)
Peer victimization at school is a pressing public health issue. Peer victimization has a deleterious impact on the victim and can lead to lifelong negative outcomes such as depression. The purpose of the present study is to examine peer victimization and potential individual, school, and peer correlates in a national sample of middle and high school students. A secondary data analysis of the School Crime and Safety survey was conducted to investigate study aims. Greater than one in 20 (7.2%) of students reported peer victimization at school. Multiple individual factors were found to increase the odds of victimization including grade level, grades received, and school avoidance among other variables. School and peer factors were also found to be significant. Study findings may be useful to school personnel for reducing peer victimization at school. Specific recommendations for school personnel are offered.